Dynamics of Fractional Holling Type-II Predator-Prey Model with Prey Refuge and Additional Food to Predator - Baishya, Chandrali (Journal of Applied Nonlinear Dynamics, 2026)
Prey refuge and additional food provided to predator help in balancing the population in ecology. In this paper, we have analysed a fractional Holling Type-II predator-prey model with prey refuge and additional food to predator. Existence and uniqueness of solution is established with the help of existing theory of fractional calculus. Sufficient conditions for existence and stability of equilibrium points are derived. Effect of prey refuge and quality of additional food to predator on balancing the population is crucially analyzed. Theoretical results are supported by numerical simulations.